A Preliminary Study on Synthesis Gas Produced by Gasification of Oil Palm Fronds - Moni, M. N. Z.; Sulaiman, S. A. (2010)
Being one of the largest oil palm producers in the world, Malaysia produces large amounts of oil palm leaves and fronds as biomass waste each year. Currently the waste is not being well managed and is disposed in controlled manner. Recent interest in palm oil empty fruit bunch (EFB) as an alternative energy source has caused a further interest in the usage of oil palm fronds (OPF) as biomass fuel feedstock. Even though that there have been many studies involving other oil palm parts, very little attention has been given for OPF. So far OPF has only been used as natural fertilizer and as domestic animal food stock. This study investigates the compatibility of OPF as gasifier feedstock and the synthesis gas produced from OPF gasification at various gasifier settings and to use the simulation evaluation results to find the best gasifier working range to yield the highest values of Lower Calorific Value (LCV) and Cold Gas Efficiency (CGE) of synthesis gas by means of simulation using a gasifier simulation program developed by Fock and Thompsen. The outcomes of the simulations are in the forms of synthesis gas composition, LCV of synthesis gas, CGE of synthesis gas and energy balance in terms of kilowatt and percentage of thermal output. The result of the study confirms the compatibility of OPF as gasifier feedstock to produce good quality synthesis gas in terms of LCV and CGE values and it was found that the operating range of a gasifier has to be 700-800oC reactor temperature, 10% feedstock moisture content and inlet air temperature close or more than reactor temperature.